2020
DOI: 10.1136/jmedgenet-2019-106676
|View full text |Cite
|
Sign up to set email alerts
|

Medical and neurobehavioural phenotypes in carriers of X-linked ichthyosis-associated genetic deletions in the UK Biobank

Abstract: BackgroundX-linked ichthyosis (XLI) is an uncommon dermatological condition resulting from a deficiency of the enzyme steroid sulfatase (STS), often caused by X-linked deletions spanning STS. Some medical comorbidities have been identified in XLI cases, but small samples of relatively young patients has limited this. STS is highly expressed in subcortical brain structures, and males with XLI and female deletion carriers appear at increased risk of developmental/mood disorders and associated traits; the neuroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 49 publications
4
66
1
Order By: Relevance
“…We identified ICD-10 unique descriptive codes that were the most common in duplication carriers (present in at least 1 in 40 (>2.5%) carriers), and that were also recorded in a significant proportion (>1.5%) of individuals in the overall male and female samples; these selection criteria, analogous to those used in our previous Xp22.31 deletion study ( 3 ), were designed to detect robust between-group effects. 13 ICD-10 codes met these criteria in the male sample ( Supplementary Material, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified ICD-10 unique descriptive codes that were the most common in duplication carriers (present in at least 1 in 40 (>2.5%) carriers), and that were also recorded in a significant proportion (>1.5%) of individuals in the overall male and female samples; these selection criteria, analogous to those used in our previous Xp22.31 deletion study ( 3 ), were designed to detect robust between-group effects. 13 ICD-10 codes met these criteria in the male sample ( Supplementary Material, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…XLI predominantly affects males, and is associated with a number of conditions including cryptorchidism and benign corneal opacities; some female deletion carriers also have corneal opacities and can exhibit prolonged/delayed labour during childbirth as a consequence of STS deficiency in the fetal portion of the placenta ( 2 ). We have recently shown that males with deletions spanning STS are at significantly increased risk of atrial fibrillation/flutter compared to male non-carriers ( 3 ). Occasional comorbidities with XLI can include focal epilepsy ( 4 ), pyloric hypertrophy, congenital defect of the abdominal wall, acute lymphoblastic leukaemia, bilateral periventricular nodular heterotopia and end-stage renal failure ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, neurodevelopmental conditions, including ADHD, autism, and mental retardation, were also observed in patients with XLI [16,17]. Recently, a study showed adult males with XLI disease-causing deletions are apparently at increased risk of cardiac arrhythmias and self-reported mood problems [10], and altered basal ganglia structure was observed in these patients [10]. In this pedigree in the present study, the patient III:6, who had ichthyosis, mental retardation, delayed speech, and history of febrile convulsion, was found to harbor a Xp22.31 deletion of 1.98 Mb, and the patient has not yet showed heart rhythm problems at the age of 35 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mutations involving solely the STS gene may present with attention de cit hyperactivity disorder (ADHD), while those with deletions including neighboring genes such as neuroligin 4 (NLGN4) may be associated with multiple neurodevelopmental disorders, including mental retardation, autism spectrum disorders (ASDs), ADHD, and seizures [4]. In addition, a recent study showed adult males with XLI disease-causing deletions are apparently at increased risk of cardiac arrhythmias and self-reported mood problems [10].…”
Section: Introductionmentioning
confidence: 99%